The exoribonuclease Polynucleotide Phosphorylase influences the virulence and stress responses of yersiniae and many other pathogens - Rosenzweig, Jason A.; Chopra, Ashok K. (Frontiers in Cellular and Infection Microbiology, 2013)
Microbes are incessantly challenged by both biotic and abiotic stressors threatening their existence. Therefore, bacterial pathogens must possess mechanisms to successfully subvert host immune defenses as well as overcome the stress associated with host-cell encounters. To achieve this, bacterial pathogens typically experience a genetic re-programming whereby anti-host/stress factors become expressed and eventually translated into effector proteins. In that vein, the bacterial host-cell induced stress-response is similar to any other abiotic stress to which bacteria respond by up-regulating specific stress-responsive genes. Following the stress encounter, bacteria must degrade unnecessary stress responsive transcripts through RNA decay mechanisms. The three pathogenic yersiniae (Yersinia pestis, Y. pseudo-tuberculosis, and Y. enterocolitica) are all psychrotropic bacteria capable of growth at 4°C; however, cold growth is dependent on the presence of an exoribonuclease, polynucleotide phosphorylase (PNPase). PNPase has also been implicated as a virulence factor in several notable pathogens including the salmonellae, Helicobacter pylori, and the yersiniae [where it typically influences the type three secretion system (TTSS)]. Further, PNPase has been shown to associate with ribonuclease E (endoribonuclease), RhlB (RNA helicase), and enolase (glycolytic enzyme) in several Gram-negative bacteria forming a large, multi-protein complex known as the RNA degradosome. This review will highlight studies demonstrating the influence of PNPase on the virulence potentials and stress responses of various bacterial pathogens as well as focusing on the degradosome-dependent and -independent roles played by PNPase in yersiniae stress responses.